CANCELLATION OF THE AUTHORITY OF THE LAND BUYING AGREEMENT AGREEMENT - Lingga Adhi Dharma (Jurnal Justiciabelen, 2022)
This study aims to analyze the cancellation of the binding agreement on the sale and purchase of land rights unilaterally. Especially those related to the validity of the sale and purchase agreement of land rights using the binding deed of sale and purchase and its cancellation. Based on the results of the study showed: (1). The sale and purchase binding agreement is an agreement born from the open nature of Book III of the Civil Code (KUHPer). This sale and purchase binding agreement arises because there are things (requirements) that have not been fulfilled or there are things (conditions) agreed by the parties to be fulfilled, for example related to payment of prices that have not been paid off. (2). changes to the price that have been agreed upon by the parties previously can only be made if there is an agreement from both parties in this case the Seller Party and the Buyer Party. This means that the adjustment to the price in the sale and purchase of land rights cannot be used as an excuse by the seller to cancel the agreement unilaterally.